The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/jfmk1010006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sagittal Plane Kinematics and Kinetics after Distal Release of Medial Hamstrings in Cerebral Palsy

Abstract: The purpose of this study is to analyze the effect of distal release of the medial hamstrings on the gait of patients who had spastic cerebral palsy. Twenty-two patients had preoperative and postoperative gait analysis. Standard parameters, such as cadence, velocity, and stride length, were evaluated, as were sagittal plane motion graphs of the pelvis, hip, knee, and ankle, in addition to sagittal plane kinetic analysis. Extension of the knee in stance phase significantly improved postoperatively (p < 0.002), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…20 A recent study has shown that simple hamstring lengthening will significantly decrease hip extension in stance phase, but interestingly, hip extension power was not affected. 21 Semitendinosus transfer to the adductor tubercle is advocated to preserve hip extension during stance phase. A study comparing hamstring lengthening and transfer showed improvement in extension power with preservation of hip extension range in the group of hamstring transfer.…”
Section: Distal Rectus Femoris Transfermentioning
confidence: 99%
“…20 A recent study has shown that simple hamstring lengthening will significantly decrease hip extension in stance phase, but interestingly, hip extension power was not affected. 21 Semitendinosus transfer to the adductor tubercle is advocated to preserve hip extension during stance phase. A study comparing hamstring lengthening and transfer showed improvement in extension power with preservation of hip extension range in the group of hamstring transfer.…”
Section: Distal Rectus Femoris Transfermentioning
confidence: 99%